Influence of the concrete DIF model on the numerical predictions of RC wall responses to blast loadings - Hao, Yifei; Hao, Hong (Pergamon, 2014)
Reliable prediction of structural responses to blast loadings requires an accurate dynamic material model. The dynamic strength of concrete material is normally higher than the static strength. Based on extensive experimental data, a number of empirical DIF (dynamic increase factor) relations have been proposed to model concrete material strength increment at high strain rates. Most of these empirical relations are obtained by fitting the scattered dynamic testing data. It is commonly acknowledged that the induced structural effects such as lateral inertia confinement effect are inevitable in high-speed impact tests. Therefore directly fitting the laboratory testing data may not necessarily obtain the true dynamic concrete material properties. Some recent studies investigated the contributions of lateral inertia and end friction confinement effects on DIF of concrete materials in laboratory tests, and proposed relations to remove these influences to obtain the true DIF for concrete materials. The present study carries out numerical simulations of a reinforced concrete wall under different blast loadings.Different DIF relations including CEB defined DIF, DIF proposed in previous studies after removing structural effect in laboratory tests, and NO DIF, i.e., neglecting dynamic strength increment, are considered in numerical simulations. Verification of the numerical model is made through the comparisons of the numerical simulation results with field test data. The results demonstrate that using the new DIF model yields the best prediction of the structural responses. The responses of a typical RC wall under blast loads with a 5 m stand-off distance but different TNT explosive charge weights are also simulated using different DIF relations. The responses of RC wall obtained from numerical models with different DIF relations of concrete material are compared. From the numerical simulation results, the range of scaled distance that DIF relation has significant influences on the numerical simulation results is identified.